The effects of probiotic supplementation on the incidence of diarrhea in cancer patients receiving radiation therapy: a systematic review with meta-analysis and trial sequential analysis of randomized controlled trials - Devaraj, Navin Kumar; Suppiah, Subapriya; Veettil, Sajesh Kalkandi; Ching, Siew Mooi; Lee, Kai Wei; Menon, Rohit Kunnath; Soo, Man Jun; Deuraseh, Inas; Hoo, Fan Kee; Sivaratnam, Dhashani (MDPI, 2019)
The protective effects of probiotic supplementation against radiation-induced diarrhea (RID) have been reported in previous systematic reviews; however so far, only non-conclusive results have been obtained. The objective of this study was to systematically update and evaluate the available evidence for probiotic supplementation. The protocol of this systematic review has been registered (CRD42018106059) with the International Prospective Register of Systematic Reviews (PROSPERO). The primary efficacy outcome was the incidence of RID. Secondary outcomes were the incidence of watery stool, soft stool, and antidiarrheal medication use. There were eight trials, and a total of 1116 participants were included in the primary analysis. Compared with placebo, probiotics were associated with a lower risk of RID [risk ratio (RR) = 0.62, 95% CI = 0.46, 0.83]. A requisite heterogeneity-adjusted trial sequential analysis indicated conclusive evidence for this beneficial effect. No statistically significant reduction in RID (RR = 0.52, 95% CI = 0.14, 1.91) was observed on subgroup analysis in patients receiving both radiation therapy and chemotherapy. However, those patients receiving only radiation therapy (RT) demonstrated significant benefit (RR = 0.61, 95% CI = 0.48, 0.78). There was a significant difference in the antidiarrheal medication use (RR = 0.54, 95% CI = 0.35, 0.84) observed with the use of probiotics. However, no significant difference was observed for the incidence of soft and watery stool. The use of probiotics is beneficial in preventing RID in patients receiving RT.